2022
DOI: 10.1039/d2an00349j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescent sensor based on an aggregation-induced emission probe for bioanalytical detection

Abstract: In recent years, with the rapid development of electrochemiluminescence (ECL) sensor, more luminophores have been designed to achieve high-throughput and reliable analysis. Impressively, after the proposed fantastic concept of “aggregation-induced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 119 publications
0
7
0
Order By: Relevance
“…By removing metal ions, covalent organic frameworks (COFs) have developed as a new class of fascinating metal-free crystalline porous ECL emitters which are attracting wide attention by virtue of their ultrahigh surface areas, favorable biocompatibility, adjustable porosity, and tunable physicochemical or luminescence activities that are on a par with MOFs [104,141]. Previous reports claimed that the ACQ effect of traditional planar luminophores in coordination polymers can be reduced or even eliminated by conjugation with AIEgens which will realize the ACQ-to-AIE transformation to obtain dramatically enhanced ECL emission [142]. Zhang et al [143] reported a pyrene-based sp 2 carbon-conjugated covalent organic framework (COF) nanosheet (Py-sp 2 c-CON) which was constructed by the C=C polycondensation of 2,2 -(1,4-phenylene)diacetonitrile (PDAN) and tetrakis(4-formylphenyl)pyrene (TFPPy).…”
Section: Cofs/hof-based Ecl Emittersmentioning
confidence: 99%
“…By removing metal ions, covalent organic frameworks (COFs) have developed as a new class of fascinating metal-free crystalline porous ECL emitters which are attracting wide attention by virtue of their ultrahigh surface areas, favorable biocompatibility, adjustable porosity, and tunable physicochemical or luminescence activities that are on a par with MOFs [104,141]. Previous reports claimed that the ACQ effect of traditional planar luminophores in coordination polymers can be reduced or even eliminated by conjugation with AIEgens which will realize the ACQ-to-AIE transformation to obtain dramatically enhanced ECL emission [142]. Zhang et al [143] reported a pyrene-based sp 2 carbon-conjugated covalent organic framework (COF) nanosheet (Py-sp 2 c-CON) which was constructed by the C=C polycondensation of 2,2 -(1,4-phenylene)diacetonitrile (PDAN) and tetrakis(4-formylphenyl)pyrene (TFPPy).…”
Section: Cofs/hof-based Ecl Emittersmentioning
confidence: 99%
“…Previous studies have demonstrated the development of ECL emitters using Ru­(bpy) 3 2+ derivatives/porphyrin-based MOFs for the construction of biosensors capable of selective multiple-target analysis. However, the presence of aggregation-caused quenching remains a challenge due to the agglomeration tendencies of the Ru (II) complex or porphyrin molecules, thereby limiting the ECL efficiency. Fortunately, the integration of aggregation-induced emission (AIE) molecules into MOFs has emerged as a promising research focus to enhance the ECL efficiency of emitters. By effectively restricting the intramolecular motions of AIE luminogens (AIEgens), AIE ligand-based MOFs can achieve high emission efficiency through the coordination-induced ECL enhancement effect. , Currently, most reported AIE-active MOFs-based ECL systems necessitate the addition of the coreactants in the detection solution to attain strong ECL emission, while the toxicity or instability of exogenous coreactants limits their further applications. In contrast, the exogenous coreactant-free ECL assay cannot only simplify the operation but also improve the reproducibility and accuracy of the ECL sensing platform.…”
Section: Introductionmentioning
confidence: 99%
“…The ECL luminophore reagent directly affects the performance of the constructed ECL biosensor. Hence, a variety of emitters have been successfully developed, such as aggregation induced emission (AIE), 13 semiconductor materials, 14 and carbon dots (CDs). 15 Among them, due to the small size, CDs can be used as macromolecular clusters to fabricate composites with porous materials, 16 which not only maintain the crystalline structure and higher luminescence characteristics, but also have high stability and good dispersion.…”
Section: Introductionmentioning
confidence: 99%